Growth in East Asia : what we can and what we cannot infer - Sarel, Michael (IMF WashingtonUS, 1996)
Looks at the nature of growth. Focuses on the growth record of Hong Kong, Korea, Singapore and Taiwan from three angles viz. the influence of government intervention; the extent to which investments and exports can be considered the main engines of growth; and, the significance for sustained growth of the economic conditions prevailing at the very beginning of the countries period of extended growth.